D ANALISIS KEBUTUHAN PENGEMBANGAN LKM TERINTEGRASI STEAM PADA MATERI EKOSISTEM UNTUK MURID FASE SMA/MA - Diva Salsabila; Zulyusri (LP2M UIN Ambon, 2026)
The development of innovative instructional materials is essential for the implementation of the Merdeka Curriculum to support student-centered learning in Biology. This study aims to develop STEAM-integrated Student Worksheets (LKM) on ecosystem topics for Phase E high school (SMA/MA) students using the Four-D (4D) development model. This study focused on the “define ” stage to analyze needs as the basis for product development. Data were collected through observations, teacher interviews, analysis of instructional documents, student needs surveys, and a literature review, all of which were analyzed descriptively. The results showed that 92.31% of students needed learning resources other than textbooks, 89.74% needed instructional materials that could be studied independently, 76.92% stated that SWs helped them understand the material, and 94.87% considered SWs important for learning. All students (100%) had never used STEAM-based worksheets, but all expressed interest in using them. These results indicate that the development of STEAM-based worksheets using a contextual approach is necessary to support more active and meaningful ecosystem based learning, as well as to develop 21st-century skills in line with the requirements of the Merdeka Curriculum.